Molecular characterisation and pathogenicity evaluation on attenuated Malaysian strains of infectious bronchitis virus - Ismail, Mohd Iswadi (2019)
Recent molecular epidemiology study detected local Malaysian variant (MV) and QX-like IBV strains circulating in commercial farms in Malaysia. Subsequent pathogenicity study showed these two strains are pathogenic in specific-pathogen-free (SPF) chickens. However, the efficacy study of commercially available vaccines in conferring protection against these two IBV strains in chickens and their molecular characteristics following attenuation in embryonated chickens eggs (ECE) have not been well studied. Hence, two previous characterised IBV isolates, MV IBS037A/2014 and QX-like IBS130/2015 strains were used as challenged viruses in vaccine efficacy and in virus attenuation studies. In the vaccine efficacy study, four commercially available IB vaccines strain Mass H120, K2, 1/96 and 4/91 were prepared as recommended by the respective manufacturers. SPF chickens were grouped according to the respective vaccine groups and vaccinated once via oculonasal route. At 21 day post-vaccination (dpv), the chickens were challenged with 105.0 EID50/0.1 ml of wildtype IBS037A/2014 or IBS130/2015. Results showed that all the vaccinated groups successfully induced antibody titre as detected by ELISA 3 weeks post vaccination. Following challenged, all the vaccinated groups showed different clinical signs and lesions of IB. Based on the protection results obtained, all the tested IBV vaccine strains were able to confer partial protection against IBS037A/2014 except Mass H120 vaccine that induced poor protection. However, all the tested vaccines were unable to provide protection against IBS130/2015 except for IBV vaccine strain 1/96 that able to confer partial protection. Virus neutralisation assay showed that the IBS037A/2014 has minor antigenic subtype difference with Mass H120 and 4/91 strains, whilst IBS130/2015 has minor antigenic subtype difference with K2 strain. The S1 sequence analysis showed that passage 70 attenuated IBS037A/2014 virus has 9% nucleotide and amino acid variations, while the passage 70 attenuated IBS130/2015 virus has 7% and 11% nucleotide and amino acid variations, respectively, when compared to their respective wildtype viruses. The attenuated IBS037A/2014 virus has majority of the amino acid variations in the hypervariable region (HVR) 1, followed by HVR 2 and 3. Meanwhile, the attenuated IBS130/2015 has the highest amino acid variations in the HVR 2, followed by HVR 3 and 1. The pathogenicity of the passage 70 attenuated viruses were compared with their respective wildtype viruses in SPF chickens. Significant differences in the microscopic lesions were detected in trachea (p=0.001) and kidney (p=0.022) of chickens inoculated with the attenuated IBS037A/2014, and trachea (p=0.001) of chickens inoculated with the attenuated IBS130/2015. The tracheal ciliary activity was significantly higher (p=0.001) in the attenuated IBS037A/2014 group, whilst no significant differences (p=0.062) in the attenuated IBS130/2015 group when compared to their respective wildtype viruses. Significant decreased in the virus copy numbers (VCN) were also detected in the trachea (p=0.013) and kidney (p=0.001) of chickens inoculated with the attenuated IBS037A/2014, and trachea of chickens inoculated with the attenuated IBS130/2015. However, a significantly increased in VCN were detected in the kidney (p=0.001) of chickens inoculated with the attenuated IBS130/2015 when compared to the wildtype viruses. In conclusion, the tested vaccine strains used in this study unable to induce complete protection against MV and QX-like. Meanwhile, the attenuated MV IBS037A/2014 showed reduced pathogenicity, whilst the attenuated QX-like IBS130/2015 is still pathogenic resembling the wildtype virus.